New Sesterterpenoids from Salvia mirzayanii Rech.f. and Esfand. Stereochemical Characterization by Computational Electronic Circular Dichroism - Mirzania, Foroogh; Moridi Farimani, Mahdi; Sarrafi, Yaghoub; Nejad Ebrahimi, Samad; Troppmair, Jakob; Kwiatkowski, Marcel; Stuppner, Hermann; Alilou, Mostafa (Frontiers in Chemistry, 2022)
Phytochemical investigation on the acetone extract of Salvia mirzayanii Rech.f. & Esfand. aﬀorded seven new isoprenoids including six new sesterterpenoids salvimirzacolide A-F (1-6), and one new nor-diterpenoid (7). Their structures were established by comprehensive spectroscopic and spectrometric data analysis (1D and 2D NMR, HRMS) and DP4+ NMR chemical shift probability calculation technique. Moreover, the absolute conﬁguration of compounds was determined by using electronic circular dichroism spectroscopy. Evaluation of antiproliferative properties of compounds isolated against four human melanoma cancer cells displayed no cytotoxic activity at the concentration range used.